ChemInform Abstract: Spin Flexoelectricity and Chiral Spin Structures in Magnetic Films. Issue 24 (June 2015) - Pyatakov, A. P.; Sergeev, A. S.; Mikailzade, F. A.; Zvezdin, A. K.
Abstract: Review: 32 refs.